Fasciola hepatica in Cavia porcellus from 10 communities in the district of Chota, Cajamarca, Peru - Torrel Pajares, Teófilo Severino (2022)
The aim of this study was to determine the prevalence of Fasciola hepática in guinea pigs from 10 communities in the Chota district, Cajamarca region, Peru. In total, 370 faecal samples collected at random from guinea pigs without distinction of age, line, type, breed or sex were analysed by the Lumbreras Rapid Sedimentation Technique. It was found a prevalence of 4.6 ± 2.13% (17/370) of guinea pigs positive to F. hepatica.